Influence of the type of post and the cementation line on the adhesive union of fiberglass posts within the root canal (Giornale Italiano di Endodonzia, 2023)
Aim: To evaluate the adhesive strength of fiberglass posts cemented in the root canal, according to the type of post and the thickness of the cement line.Methodology: Forty primary bovine incisors, 17 mm long, were endodontically treated. After seven days, the teeth were unfilled and prepared to receive the 13 mm posts. The roots were randomly divided into four groups according to the type of post (Reforpost® cylindrical post and Exacto® conical post) and the thickness of the cementation line. The posts were cemented with RelyX U200® within the root canal. The roots were sectioned, thus obtaining specimens with an average thickness of 1.92 mm in each of the root thirds (cervical and middle). The specimens were submitted to the push-out test. After performing the test, the fractured samples were analyzed under a stereomicroscope to determine the fracture pattern. The data obtained were treated by the one-way ANOVA test, followed by the Tukey test, and the non-parametric t test (α=0.05).Results: There was a statistical difference between the groups regarding the different root positions analyzed (P